2015
DOI: 10.1111/age.12319
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between wild greylag and European domestic geese based on mitochondrial DNA

Abstract: The origins of the European domestic goose are uncertain. The available information comes from archaeological findings and historical literature, but genetic evidence has hitherto been scarce. The domestic goose in Europe is derived from the greylag goose (Anser anser), but it is not known where the initial domestication took place and which of the two subspecies of greylag goose was ancestral. We aimed to determine the amount and geographical distribution of genetic diversity in modern populations of greylag … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 53 publications
1
39
2
2
Order By: Relevance
“…All 51 individuals sequenced were found to be monomorphic in the amplified fragment of the CR, providing a single haplotype. After comparison with published studies, our sequence was identified as the haplotype E7 that was only found in birds from Prespa Lakes in Heikkinen et al (2015). All microsatellite markers were found to be polymorphic in the population and the number of alleles per locus ranged from two (loci Aph19, Hhiµ1b) to nine (locus Ans02; Additional file 1: Table S2).…”
Section: Genetic Diversitymentioning
confidence: 85%
See 4 more Smart Citations
“…All 51 individuals sequenced were found to be monomorphic in the amplified fragment of the CR, providing a single haplotype. After comparison with published studies, our sequence was identified as the haplotype E7 that was only found in birds from Prespa Lakes in Heikkinen et al (2015). All microsatellite markers were found to be polymorphic in the population and the number of alleles per locus ranged from two (loci Aph19, Hhiµ1b) to nine (locus Ans02; Additional file 1: Table S2).…”
Section: Genetic Diversitymentioning
confidence: 85%
“…All extractions were performed with the DNeasy Blood and Tissue kit (Qiagen) following the manufacturer's protocol. For mtDNA analyses we amplified a 394 bp fragment near the 5′ end of the Control Region (CR), using primers L16642 and H411ANX (Ruokonen et al 2000;Heikkinen et al 2015) for 51 individuals. Each 12.5 μL PCR reaction contained 1 unit of Taq DNA polymerase (Finnzymes), 1× reaction buffer, 1.5 mM of MgCl 2 , 0.2 mM of each dNTP, 0.5 mM of each primer and 50 ng of DNA template.…”
Section: Laboratory Proceduresmentioning
confidence: 99%
See 3 more Smart Citations